The Involvement of the Twelfth Grade English Textbook in Jordan: An Analytical Study - RAMI ABU SA'ALEEK (Indonesian Research Journal in Education |IRJE|, 2018)
The English language textbook for the twelfth grade is relatively a new edition.Thus, with the importance of the textbook in language learning, this study aimed at investigating the involvement degree for the 12th grade English language textbook in Jordan through analyzing the presentation of educational contents and activities. To achieve this purpose, Rummy’s (1968) method was used to collect the data. The sample of the study was 15% of the book pages to examine the involvement of the educational content. The sample also consisted of all the activities with total (136) activities. The findings of the study showed that the decrease of students' involvement in educational content in the English language textbook for 12th grade and were not in the satisfactory range adopted by Rummy’s (1968) method, reaching the value to (0.18). The study also revealed that the involvement level of the activities was excellent with a coefficient (1.41). Based on these results, some implications are presented such as revising the content to focus on higher thinking skills, not fact or conclusions only.